Algorithm of control systems required accuracy providing under the undetermined external disturbances - Zbrutskyi, O.; Zagirska, I.; Stetsenko, T. (Видавництво Львівської політехніки, 2011)
New control algorithm and algorithm for providing required quality are defined. It based on comparison the forecast system condition, allowance conditions value, dynamic system properties and undetermined external disturbances compensation.
Keywords: control algorithm; disturbance compensation; decision making